Chemical vapor deposition for few‐layer two‐dimensional materials - Qing Zhang; Dechao Geng; Wenping Hu (SmartMat, 2023)
Abstract Chemical vapor deposition (CVD) approach offers a controllable strategy for preparing large‐area and high‐quality few‐layer (mainly bilayer or trilayer) twisted or untwisted two‐dimensional (2D) materials, and is predicted to boost the development of 2D materials from laboratory research to industrial applications.